2020
DOI: 10.2298/tsci190528039l
|View full text |Cite
|
Sign up to set email alerts
|

Medical molecules of waste Chinese buckeye seed from pharmacy

Abstract: Fourier transform infrared (FT-IR) spectroscopy and gas chromatography-mass spectrometer (GC-MS) were used to analyze organic solvent extracts of Populus tomentosa Carriere, the results show that the Chinese Buckeye Seed is mainly healthy and rich in Chinese Buckeye Seed extracts,The main representative of the active ingredient are Furfural, Isosorbide Dinitrate, Catechol, 1,2-Benzenediol, 4-methyl-, 3-Amino-s-triazole, 2,3-Quinoxalinedione, 1,4-dihydro-, Docosanoic acid, Medetomidine. Chinese Buckeye Seed ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…S. holocarpa wood’s methanol, benzene/ethanol and ethanol/methanol three extracts of light transmittance have changed in different degrees. The results showed that the main organic chemical components were ketones, acids, ethers, and so on [ 41 ]. In particular, the structure containing O and fat almost disappeared, which in turn showed that the intensity of the absorption peaks in the corresponding band weakened to varying degrees.…”
Section: Resultsmentioning
confidence: 99%
“…S. holocarpa wood’s methanol, benzene/ethanol and ethanol/methanol three extracts of light transmittance have changed in different degrees. The results showed that the main organic chemical components were ketones, acids, ethers, and so on [ 41 ]. In particular, the structure containing O and fat almost disappeared, which in turn showed that the intensity of the absorption peaks in the corresponding band weakened to varying degrees.…”
Section: Resultsmentioning
confidence: 99%